Students' Perceptions About Teaching Profession: Emotional Intelligence, Critical Thinking, and Locus of Control - Zuhri Saputra Hutabarat; Phousith Phongsavath (Journal of Innovation in Educational and Cultural Research, 2023)
This study aims to analyze students' perceptions of the teaching profession in increasing self-confidence to continue to feel worthy and ready to become professional and competent teachers. The approach used in this research is a quantitative search design approach using a survey model. The participants in this study were recruited from economics education students who had completed teaching internship programs. The data were analyzed using Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), and Structural Equation Modeling (SEM). The following are the research results: 1) Student teachers enrich meaningful experiential insights through problems and problem-solving in self-control to build a positive image regarding student perceptions of the teaching profession; 3) With good emotional intelligence, student teachers can develop their potential by adding to their insights in developing their qualifications to become teachers; 4) Student teachers can adapt to any circumstances, solve learning problems effectively and efficiently, and make the class atmosphere more enjoyable. This research implies that higher education institutions add more scientific studies about the teaching profession through field practice programs at schools and in every subject in the education department. Therefore, we conclude that students' perceptions of the teaching profession since students entered college will broaden their knowledge so that they can follow every development in the world of education so that they are better prepared to become professional and competent teachers.